2019
DOI: 10.1177/2396987319828160
|View full text |Cite
|
Sign up to set email alerts
|

Preventable poor outcome from rebleeding by emergency aneurysm occlusion in patients with aneurysmal subarachnoid haemorrhage

Abstract: Introduction: The risk of rebleeding is highest during the initial hours after aneurysmal subarachnoid haemorrhage (aSAH), but the aneurysm is not occluded in all patients immediately after admission. Our aim was to determine the proportion of aSAH patients with poor outcome from early in-hospital rebleeding that can be prevented by three emergency aneurysm occlusion regimes. Patients and methods: From our prospectively collected database, we retrieved from all aSAH patients admitted between July 2007 and July… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…However, since the risk of rebleeding in patients undergoing early aneurysm occlusion is around 10% to 15%, and strict BP control does not eliminate rebleeding, such an RCT would need to include several thousands of patients, making it an ambitious endeavour. 33,34 Since emergency clipping, that is clipping within the initial hours after admission on a 24/7 basis, has a modest treatment effect, if at all, and its cost-effectiveness is uncertain due to the high burden on resources, 35 a RCT of BP lowering should be a high priority, as it is a promising strategy to improve outcome that could be initiated during the transport of patients by ambulance to an appropriate facility.…”
Section: Evidence To Support Bp Control After Sahmentioning
confidence: 99%
“…However, since the risk of rebleeding in patients undergoing early aneurysm occlusion is around 10% to 15%, and strict BP control does not eliminate rebleeding, such an RCT would need to include several thousands of patients, making it an ambitious endeavour. 33,34 Since emergency clipping, that is clipping within the initial hours after admission on a 24/7 basis, has a modest treatment effect, if at all, and its cost-effectiveness is uncertain due to the high burden on resources, 35 a RCT of BP lowering should be a high priority, as it is a promising strategy to improve outcome that could be initiated during the transport of patients by ambulance to an appropriate facility.…”
Section: Evidence To Support Bp Control After Sahmentioning
confidence: 99%
“…The current evidence suggests that effective aneurysm treatment as early as possible is the best way to reduce or even to prevent rebleeding after hemorrhage (10)(11)(12). However, not all patients are treated immediately within a few hours after admission (13,14). Therefore, a more effective treatment modality, not just aneurysm surgery alone, is still needed before the aneurysm is secured.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, early treatment of responsible ruptured aneurysms was the basic principles in managing aSAH patients. Early treatment could significantly reduce re-bleeding rate and improve clinical outcomes, especially in poorgrade patients [8][9][10]. Menno et al reported the time interval between initial hemorrhage and treatment, with 76% patients treated by coiling or clipping within 24 h after diagnosis [11].…”
Section: Introductionmentioning
confidence: 99%